The Death Penalty in Legal Literature: A Study of Indonesian Law and International Human Rights - Fauzan Fauzan (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2021)
The use of the death penalty in criminal law to achieve the aims of criminal law has sparked much controversy among criminal law professionals. The advantages and disadvantages of adopting death punishment to meet the aims of criminal law, such as providing a sense of security, justice, and so on. In the hierarchy of rules and regulations in Indonesia, the 1945 Constitution is the highest source of legislation. Article 28 (a) of the Indonesian constitution guarantees the right to life and provides that everyone has the right to survive and defend his or her life and existence. As a result, the right to life is a constitutional guarantee. Thus the right to life is a constitutional right. The United Nations also issued a guide entitled Safeguards Guaranteeing Protection of the Rights of Those Facing the Death Penalty through UN Economic and Social Council Resolution 1984/50, dated 25 May 1984. This guide clarifies discussions on the practice of the death penalty under the International Covenant on Civil and Political Rights.